Micromechanical and microstructural analysis of Fe-rich plasma slag-based inorganic polymers. (April 2021) - Mast, Bram; Fransis, Sylke; Vandoren, Bram; Cambriani, Andrea; Schroeyers, Wouter; Pontikes, Yiannis; Samyn, Pieter; Schreurs, Sonja
Abstract: The development of new materials such as inorganic polymers (IPs) requires a deep understanding of the effect of the microstructural and the micromechanical properties on the strength. In this study, digital image processing technique were used to characterize SEM images of different IP microstructures. Via nanoindentation, the micromechanical properties were determined. Effects of changing the precursor fineness and the SiO2 /Na2 O (1.2–2.0) and H2 O/Na2 O (20.0–29.0) molar ratio of the activating solution (AS) on the properties of plasma slag-based IPs were studied. With a decreasing SiO2 /Na2 O molar ratio, the reactivity increased and more binder was formed not affecting the binder elastic properties, though leading to an increased strength. A decrease in H2 O/Na2 O molar ratio slightly favored the reactivity, with no extra binder formation, but with an increased elastic modulus of the binder. Damage initiation and propagation in the IP samples at the microscale was simulated using realistic microstructures and local mechanical properties. The effect of the elastic modulus of the binder phase on the strain softening was found to be negligible. Graphical abstract: Image 1